EKOLOGI SPIRITUAL: SOLUSI KRISIS LINGKUNGAN - Irawan, Irawan (Scientia: Jurnal Hasil Penelitian, 2017)
This article explains that the environmental crisis which is done by human being. This environmental damage is caused by the belief that the realm is offered by God to be utilized by human beings as khalifah on earth with the fullest extent. Through the perennial philosophy approach, this paper explores the importance of spiritual values ​​in human beings when dealing with ecology/environment. This paper concludes that nature and man are equally fitrah (holy). However, there is a very basic difference between the two, that is, humans are gifted by reason, whereas nature does not. Therefore: a) the central role of man is the servant of the universe; b) there is an urgent need for Muslims to improve their behavior to live more harmoniously with nature than humans; c) the moral and ethical dimensions of human beings are essential in order to treat nature with a friendly and courteous manner; d) the spiritual values ​​in man must always be implied in every line of life when dealing with nature, and e. the task of man sent to the universe is inseparable from the concept of tawhid, khalifah, amanah, akhirah, adl, and mizan.